TRADISI IJTIHAD: MENGEMBALIKAN SEMANGAT PROGRESIVITAS ISLAM - Fawaid, Ah. (ULUL ALBAB Jurnal Studi Islam, 2010)
The tradition of ijtihad became a rare activity conducted. This tradition on the other hand seems to be the authority of the religious elite and another hand, yet the tradition of ijtihad which should be further developed. It became the spirit of Islamic progressivity. Without this tradition, Islam seems to be frozen and stutter for the challenges of the times. It must be realized that the current challenge may be resolved not merely refer to the creativity of the past. Contemporary challenges must be faced and solved by the present creativity as well. Creativity is a time only in the context of time resolve the problem and not always just as drawn to the matter at different times. Any period has a different way and solution in accordance with the challenges of his time. Similarly, each community has a different solution when faced with problems, even at the same time and same problem. This is where the interpretation of reality gave birth to the diversity of interpretation of a role as well as the diversity of truth. And moving the tradition of ijtihad is one of the efforts to mobilize Islam.